Study guides

Q: 10y plus 23 equals 4y plus 26 equals?

Write your answer...

Submit

Related questions

y = ½ (6y = 3)

23

26 - 21 = 5 or 24 - 23 = 1

15x26=390

13+13=26

How about 20 plus 6 equals 26 as one example

-26

2a + 2b = 26 2b + c = 22 ===> b = 11 - c/2 4c + 2b = 46 ===> b = 23 - 2c From the 2nd and 3rd equations: 11 - c/2 = 23 - 2c 22 - c = 46 - 4c 22 - 46 = -4c + c ===> -24 = -3c ===> c = 8 Substitute c=8 into the 3rd equation: b = 23 - 16 = 7 Substitute b=7 into the 1st equation: 2a + 14 = 26 2a = 12 ===> a = 6

23/9 + 1/3 = 23/9 + 3/9 = 26/9 = 2 8/9

26

26

26 + 8 = 34

n = 26

40

26

105.

(6, -4)

8x - 10y = 27x - 5y = 13First, we need to eliminate one of the variables. For this, we would like to have them with the same coefficient but different sign. We can do this if we multiply by -2 the second equation.8x - 10y = 2-2(7x - 5y) = -2(13)8x - 10y = 2-14x +10y = -26Now, we can add both equations, and solve for x.(8x - 10y) + (-14x + 10y) = (2) + (-26)(8x - 14x) +(-10y + 10y) = (2 - 26)-6x = - 24-6x/-6 = - 24/-6x = 4Substitute 4 for x in the first equation:8x - 10y = 28(4) - 10y = 232 - 10y = 232 - 32 - 10y = 2 - 32-10y = -30-10y/-10 = -30/-10y = 3Thus, the solution of the system is (4, 3).Check:

49

26

64

26

49

104

The answer is 156. Simply add the numbers together like you would for two plus two. To check your work, a calculator is the best option. Another option is doing 26 multiplied by 6 where you aso get 156